2017
DOI: 10.3354/meps12071
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in lunar timing of larval release of two brooding pocilloporid corals in an internal tide‑induced upwelling reef

Abstract: The environmental conditions in shallow marine environments vary on multiple temporal scales, but under the influence of climate change, these conditions are likely to change in frequency and magnitude. Phenotypic plasticity is one mechanism by which organisms can respond to this complex environmental challenge. Plasticity of reproductive timing may have beneficial value, especially for species that reproduce multiple times annually. In this study, we quantified the lunar periodicity of larval release by 2 bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Cold, upwelled water eddies would help the coral reefs have a short low temperature recovery period during episodes of extreme high sea temperatures thereby reducing the chance of bleaching. A recent study has also highlighted that the two varieties of Nanwan Bay coral are highly adaptable and may adjust their spawning times to survive (Fan et al, 2017). Therefore, continuous monitoring of eddy activity and SST variability is vital for promoting coral health in Nanwan Bay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cold, upwelled water eddies would help the coral reefs have a short low temperature recovery period during episodes of extreme high sea temperatures thereby reducing the chance of bleaching. A recent study has also highlighted that the two varieties of Nanwan Bay coral are highly adaptable and may adjust their spawning times to survive (Fan et al, 2017). Therefore, continuous monitoring of eddy activity and SST variability is vital for promoting coral health in Nanwan Bay.…”
Section: Discussionmentioning
confidence: 99%
“…The drastic changes in the daily SST may make it difficult for some corals to survive or make cause some coral populations to develop natural adaptation (Keshavmurthy et al, 2014). Fan et al (2017) found that two types of corals have evolved physiological mechanisms to respond to changes in the sea temperature and to self‐adjust their reproductive timing; that is, sea temperature fluctuations caused by tidal flow and strong upwelling may regulate the timing of the spawning and larval release of coral. Therefore, the upwelling area in Nanwan Bay may act as a shelter for coral reefs under the threat of ocean warming.…”
Section: Introductionmentioning
confidence: 99%
“…However, assuming that coral fecundity at least was not greater in 2016 versus 2014 or 2015, which is reasonable given the impairment of reproduction that might be expected from thermal bleaching [ 34 , 35 ], then high coral recruitment in 2016 may reflect an effect of temperature on the timing of spawning, fertilization and the development of pelagic larvae, or the growth of the recruits they produce. Seawater temperature has long been known to affect the phenology of coral spawning [ 37 , 71 ], with warm temperatures advancing release relative to cool temperatures [ 37 , 51 ], and recently this relationship has been quantified for two brooding pocilloporids in Taiwan [ 37 ]. For these corals, the mean lunar day of release of brooded larvae advanced with rising temperature, and would advance 12–15% (≈ 1 d) with an increase from 28°C to 29°C [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…El Niño conditions also have effects that are more subtle than bleaching [ 8 ], as might be expected from the pervasive influences of temperature on poikilothermic organisms [ 33 ]. For scleractinians, these can include impaired reproduction [ 34 , 35 ] that can last more than a year following bleaching [ 34 ], probably through the consumption of energy reserves when deprived of carbon from their Symbiodinium algal endosymbionts [ 34 , 36 ], and perhaps by shifts in reproductive phenology [ 37 ]. The negative impacts of high temperature and bleaching on coral reproduction offer one explanation for reduced coral recruitment following El Niños [ 22 , 38 , 39 ], as well as shifts in the taxonomic composition of recruiting corals [ 39 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that “bet-hedging” or environmental tuning by the parents may result in release of larvae timed to favorable conditions. For example, a shift in reproductive timing of coral planulation with change in temperature across season was recently documented (Fan et al, 2017). In this case, seasonal acclimatization in the parents resulted in change in summer planulae release timing, which minimizes planulae release during strong, likely stressful, upwelling-induced temperature fluctuations of ~10°C (Lee, Chao, Fan, Wang, & Liang, 1997).…”
Section: Discussionmentioning
confidence: 99%